Usage of slurry oil for the preparation of crumb-rubber-modified asphalt emulsions. (1st February 2015) - Zhou, Xiaolong; Wang, Feng; Yuan, Xulu; Kuang, Minming; Song, Yueqin; Li, Chenglie
Highlights: Progress to develop modified asphalt emulsions by using crumb rubber (CR). A method to prepare CR modified asphalt emulsions. Effect of FCC slurry oil on the emulsification characters and product properties. Characterization and discussion from routine tests and DSR measurements. Abstract: Due to the increased performance-related requirements on the products from aqueous asphalt emulsions, scrap tire crumb rubber (CR) has been successfully applied as a modifier. An approach to prepare CR-modified asphalt emulsions with satisfactory emulsifying characters and resultant product properties has been studied. In this paper, microwave pretreated CR was first reacted with asphalt materials under optimum conditions. Next, the CR/asphalt mixture (CRMA) was blended with slurry oil (decant slurry oil) from a fluid catalytic cracking process (FCC) in refineries to form an emulsifiable asphalt binder. In this work, 3% slurry oil content in this CRMA was demonstrated to be sufficient for the emulsification via the addition of water and an emulsifier. Under the optimum environmental factors to prepare the emulsions, as exemplified in this work, the resultant CRMA is capable of being well emulsified. The asphalt emulsions and related products produced in this work are able to meet the requirements. The effects of CR and slurry oil are studied by using the results from routine tests and dynamic shear rheometer (DSR) measurements. The results revealed that asphalt binders, obtained after these asphalt emulsions are broken, have improved road performance at high temperature, compared to that from the original asphalt. The consistency has also been increased. The CR powder asphalt modifier is an alternative to virgin polymer in the preparation of modified asphalt emulsions. The CR powder has significant environmental and economic advantages. A method to directly use slurry oil in a large amount was developed. The results in this work pave the way to prepare CR and slurry oil-modified asphalt emulsions.